The Phylogeny of Quasars and the Ontogeny of Their Central Black Holes - Fraix-Burnet, Didier; Marziani, Paola; D'Onofrio, Mauro; Dultzin, Deborah (Frontiers in Astronomy and Space Sciences, 2017)
The connection between multifrequency quasar observational and physical parameters related to accretion processes is still open to debate. In the last 20 year, Eigenvector 1-based approaches developed since the early papers by Boroson and Green (1992) and Sulentic et al. (2000b) have been proved to be a remarkably powerful tool to investigate this issue, and have led to the definition of a quasar “main sequence”. In this paper we perform a cladistic analysis on two samples of 215 and 85 low-z quasars (z 0.7) which were studied in several previous works and which offer a satisfactory coverage of the Eigenvector 1-derived main sequence. The data encompass accurate measurements of observational parameters which represents key aspects associated with the structural diversity of quasars. Cladistics is able to group sources radiating at higher Eddington ratios, as well as to separate radio-quiet (RQ) and radio-loud (RL) quasars. The analysis suggests a black hole mass threshold for powerful radio emission and also properly distinguishes core-dominated and lobe-dominated quasars, in accordance with the basic tenet of RL unification schemes. Considering that black hole mass provides a sort of “arrow of time” of nuclear activity, a phylogenetic interpretation becomes possible if cladistic trees are rooted on black hole mass: the ontogeny of black holes is represented by their monotonic increase in mass. More massive radio-quiet Population B sources at low-z become a more evolved counterpart of Population A i.e., wind dominated sources to which the “local” Narrow-Line Seyfert 1s belong.